Sugarcane bagasse biochar pellets for removal of caffeine, norfloxacin, and ciprofloxacin in aqueous samples - Fonsêca, Mateus Cottorello; Marasco Júnior, César Augusto; Dias, Diógenes dos Santos; da Silva, João Pedro; Lamarca, Rafaela Silva; Ribeiro, Clóvis Augusto; Pires, Lorena Oliveira; Lima Gomes, Paulo Clairmont Feitosa (Eclética Química, 2022)
This work investigates the physicochemical properties of a biochar obtained from sugarcane bagasse by torrefaction at four different temperatures (260, 270, 280, and 290 °C), without chemical or physical activation. The biochar was characterized by thermogravimetric and proximate analysis, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy, together with measurements of point of zero charge, pH, elemental composition, and surface area. Evaluation regarding the efficiency of the biochar employed as an adsorbent for the removal of caffeine, ciprofloxacin, and norfloxacin in wastewater samples. The assays were performed in batch vessels filled with lab-made sewage spiked with caffeine at 5.00 µg L–1 and with ciprofloxacin and norfloxacin at 10.0 µg L–1. These compounds were studied separately. The thermogravimetry data demonstrated that increasing the torrefaction temperature led to generation of a greater amount of fixed carbon, as well as loss of volatile materials and removal of non-condensable compounds. This was corroborated by the FTIR analyses, where a higher temperature led to higher intensity of bands corresponding to methyl, methylene, and C=C bonds. The biochar produced at 280 °C presented the best stability, with adsorption efficiencies for removal from the lab-made sewage of 91% (norfloxacin), 81% (ciprofloxacin), and 58% (caffeine).